Carrier based synchronous control and performance analysis of an S-PSI using PV for microgrid applications - Rahman, Tawfikur; Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn; Alam, A. H. M. Zahirul; Mostafa, Mohammad Golam; Rahman, M. Wahidur (IEEE Explore, 2018)
This paper proposes a carrier-based pulse width modulation (CB-PWM) method with synchronous switching technique for a Vienna rectifier. In this paper, a Vienna rectifier is one of the 3-level converter topologies. It is similar to a 3-level T-type topology the used back-to-back switches. When CB-PWM switching method is used, a Vienna rectifier is operated with six PWM signals. On the other hand, when the back-to-back switches are synchronized, PWM signals can be reduced to three from six. However, the synchronous switching method has a problem that the current distortion around zero-crossing point is worse than one of the conventional CB-PWM switching method. To improve current distortions, this paper proposes a reactive current injection technique. The performance and effectiveness of the proposed synchronous switching method are verified by simulation with a 5-kW Vienna rectifier.